Crystallographic and optical properties of ZnO nanoparticles prepared by two different methods - Flores Mariños, Betty Mercedes (2025)
This research presents the synthesis of nanoparticles of ZnO (Nps-ZnO) obtained by two methods: chemical precipitation (method 1) and combustion in solution (method 2). The effect of each method on the crystallographic properties of Nps-ZnO is studied. The Nps-ZnO obtained present, according to EDS analysis, an atomic Zn: O ratio of 0.95 and 1.36 when two methods were used respectively. The formation of Nps-ZnO with Wurtzite-type hexagonal arrangement is confirmed with XRD analysis. XRD results show there is not a big difference between the lattice parameters and interplanar spacing for the samples obtained by the two synthesis methods. However, the Nps-ZnO obtained by chemical precipitation show higher values of dislocation density (1.780 × 10− 3) nm− 2 than those obtained by combustion in solution (0.152 × 10− 3) nm− 2. A similar behavior is observed with the micro-strain values (2.137 × 10− 3-6.388 × 10− 3) and (1.170 × 10− 3-1.971 × 10− 3), respectively. TEM images show nanoparticles with mean diameters between 17.2 ± 10.8 nm and 73.4 ± 6.0 nm when the method of chemical precipitation and combustion in solution were applied, respectively. Larger and semi-square nanoparticles are formed with the combustion in solution method is applied. Size of Nps-ZnO estimated from TEM images analysis, Debye-Scherer’s formula and Rietveld refinement are highly inter-correlated. Finally, the Nps-ZnO presented a narrow bandgap of 3.19 eV and 3.16 eV, a value lower than that of the bulk material (3.7 eV). No drastic change in bandgap is observed for samples synthesized with two different methods.